Digital Learning Media Assisted by Quizizz Application (METALIQ) on Science Content of Ecosystem Topic for Sixth Grade Elementary School - Nanda Sekar Astafiria; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2021)
This study aims to produce â€œMETALIQâ€ which was developed on the topic of Ecosystems for the sixth-grade elementary school students. This research was a development research based on the ADDIE model procedure. The subject of this research was